VISUAL IMPAIREMENT AND FALLS AS RISK FACTORS OF ORTHOPEDIC FRACTURES - MUGABE, Herbert (Medicinski podmladak, 2023)
The musculoskeletal system represents one of the most affected systems in general traumatology. Fractures of the locomotor system and their effects are among the most severe and demanding injuries for the community in general and for the health system in particular. Different risk factors for fractures have been established in the last 4 decades with falls representing the main cause. Given the fact that vision plays a key role in maintaining gait and balance, various conditions of visual impairments have also been associated with an increase in fall-related injuries, and fractures of the locomotor system, especially in older population. Moreover, with an increased life expectancy, there is a rise in the number of visually impaired individuals in the population, as well as the number of falls and fractures. In our study, we did a review of the incidence and risk factors of musculoskeletal system fractures and falls, and the incidence of visual impairments in the general population. We also did a review of different types of visual impairments that have been studied as potential risk factors for fractures, falls and soft tissue injuries of the hand and if there has been any association between these specific visual impairments and the risk of falling, getting a fracture or a soft tissue injury of the hand.